Research on Determinants of Operational Risks in Chinese Commercial Banks - Wang, Xinyi (2018)
Operational risk is an ancient risk in the banking industry. It is listed by the Basel Committee (BCBS) as one of the three major risks in the banking industry, whose importance and urgency have received worldwide attention. With the rapid increase of the global economic aggregate and the deepening of globalization, the operational risk has become a bigger and bigger part of the total risk, and it has become the most important risk faced by some banks. This paper aims to use the game theory method to deeply explore the determinants of commercial banks' operational risk under the finite theory hypothesis, and to explore the reality that affects the operational risks of Chinese commercial banks by combining China's specific national conditions with the determinants of commercial banks' operational risks. Factors, and finally on this basis, try to propose ways to prevent and control the operational risks of Chinese commercial banks.